Key Words 11b: The Carnival - W. Murray
"Key Words with Peter and Jane" uses the most frequently met words in the English language as a starting point for learning to read successfully and confidently. The Key Words reading scheme is scientifically researched and world renowned. In book "11b", Peter and Jane build a space rocket and introduce 76 new words, including 'carnival', 'myself', 'glass' and 'above'. Once this book has been completed, the child moves on to book "11c". "The Key Words with Peter and Jane" books work because each of the key words is introduced gradually and repeated frequently. This builds confidence in children when they recognise these key words on sight (also known as the 'look and say' method of learning). Examples of key words the, one, two, he. There are 12 levels, each with 3 a, b, and c. "Series a": gradually introduces new words. "Series b": provides further practise of words featured in the 'a' series. "Series c": links reading with writing and phonics. All the words that have been introduced in each 'a' and 'b' book are also reinforced in the 'c' books.